Hubungan Pengatahuan Ibu Dengan Kebiasan Membaca Label Kemasan Pangan Pada Ibu Yang Mempunyai Bayi Usia 6-12 Bulan di Wilayah Kerja Puskesmas Kepatihan Kecamatan Menganti Kabupaten Gresik - Winiastri, Dinda; Darban, Harlina (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
Food label is any information about the food in the form of images, text, a combination of both, or other forms that are included in the packaging of food. The role of the labels on food products is necessing in educational advice for the community and into value added products and selecting food products is needed.The purpose of this study is to study the relationship of knowledge with the knowledge of food Food labeling in mother who have baby aged 6-12 months In the Working Area Health Center Kepatihan Menganti District Gresik. This research is an analytic correlation with cross sectional study design sampling techniques in this study using proportional random sampling technique, the sample in this study of 37 mother who have baby aged 6-12 months. The result of this research indicate that there is correlation between mother's knowledge with the habit of reading food packaging label in Working Area of Kepatihan Community Health Center Menganti Sub-district of Gresik Regency by using statistic spearmen test obtained p = 0,010 with a = 0,05 (p <0,05).To improve mother's knowledge about the habit of reading food labeling do counseling about food labeling by health personnel so that mother who have baby get used to read food labeling every time they will buy porduct and utilize information on food labeling in deciding food choice and to increase knowledge about food labeling. mother who have baby do not read food labeling will have an impact on infant health such as: toxicity, obesity, and allergies.